Analisis Struktur Naratif Dalam Geguritan Jayaprana - Nyoman Suardika (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Literary work is a work that contains values and teachings that can be used as a way of life. A literary work, especially an old (traditional) literary work, is usually regional in nature or still contains local culture in its creation. One example of an old (traditional) literary work is Geguritan Jayaprana. The type of research used in this research is descriptive with a qualitative approach. The data source of this research is primary data or data obtained directly from the original source, namely the Geguritan Jayaprana translation book by Ketut Ginarsa. Data collection is done by reading repeatedly on the object of research. The results showed that the analysis of the narrative structure in Geguritan Jayaprana, namely the incidents contained in this geguritan are several incidents. The plot used is a straight or forward plot, which consists of five stages. There are three elements of the background in this Jayaprana Geguritan, namely the setting of the place, the setting of time, and the setting of the atmosphere. The characters and characterizations in Geguritan Jayaprana are the main character and the complementary character. The theme in Geguritan Jayaprana is loyalty. The message that can be learned from Geguritan Jayaprana is that loyalty is an attitude that must be possessed by a person, even though it can be painful, but with loyalty humans will have a better quality of life.